(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, we will discuss with you a great state-cushan Empire, which was one of the strongest countries in the world in its day and united the property of present-day Southern Uzbekistan, Southern Tajikistan, Afghanistan, Pakistan, and India.